Gesneriaceae endémicas del Perú - Salinas, Irayda (2006)
The Gesneriaceae are represented in Peru by 31 genera and 141 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly herbs and shrubs. Here we recognize as endemics 36 species and three varieties in twelve genera. Besleria is the genus with the largest number of endemic species. Peru’s endemic Gesneriaceae are found in the Humid Lowland Amazonian Forest and Very Humid Montane Forest regions, between 100 and 2900 m elevation. Eight endemic taxa have been recorded within the Peruvian protected areas system.